Investigating and determining psychological factors affecting women’s sexual function - Kazemi Mojarad, Maliheh; Khalatbari, Javad; Moazedian, Ameneh; Sotodehasl, Nemat (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Several factors have a role in the formation of sexual function, some of which have been identified in previous studies. This study was conducted to investigate other factors that may not have been identified in previous studies. In this regard, the aim of this study was to investigate and determine the psychological factors affecting women’s sexual function. Methods: The method of this study was qualitative with interpretive approach and themed analysis method. Based on the purposeful sampling method, the data of this study were saturated with 13 married women from April to June 2020. In-depth semi-structured interview method was used to collect data. Data were analyzed by themed analysis method. Results: Findings showed the categories explained "sexual knowledge", "sexual attitude", "sexual self-efficacy", "sexual intimacy", "sexual redress" and "sexual self-efficacy". Conclusion: It seems that when women perform sexual activities for themselves certain rights such as demanding sexual activity, accepting the existence of intimacy in sexual relationships, etc. They believe that they achieve a positive perception about sexual activity in marital relationships, which can contribute to optimal sexual function.